Missed presentations, missed opportunities: A cross‐sectional study of mental health presentation undercounting in the emergency department. (29th November 2022) - Werkmeister, Catherine; Cunningham, Ruth; Freeland, Abigail; Stanley, James; Every‐Palmer, Susanna; Kuehl, Silke
Abstract: Objectives: The burden of mental illness is increasing across developed countries. EDs are often used as access points by people experiencing mental health crises, with such rising demand in Australasia. Accurate data is critical to track and address this need, but research suggests that current data collection methods undercount mental health presentations to the EDs. The present study aimed to quantify and characterise ED mental health presentations that were not identified by usual clinical coding processes. Methods: From almost 50 000 presentations to a large regional ED over 12 months, 1988 were mental health‐related as identified via discharge diagnoses and ICD‐10 codes. For a further 384 presentations, it was ambiguous whether they were mental health‐related. For these, free‐text clinical notes were reviewed to identify mental health‐related presentation missed by clinical coding practices. Demographic information, time of presentation, recent use of secondary mental health services and disposition from ED were extracted and analysed. Results: An additional 91 mental health presentations were found by review of clinical notes; 4.6% (95% confidence interval 3.7–5.6) more presentations than identified via screening of discharge codes. In these 'missed' cases, clinicians had documented clear mental health symptoms but without coding the corresponding diagnosis. Existing clinical coding practices were less accurate for patients who were not current or recent users of mental health services, and for those who were discharged directly from ED. Conclusions: The present study demonstrates that ED mental health presentations may be underestimated by nearly 5%, revealing greater mental health demand than current figures suggest. Abstract : A proportion of patients presenting to emergency departments for mental health are not identified by usual clinical coding processes. This cross‐sectional study examined presentations over 12 months to one New Zealand ED to quantify and characterise these 'missed' mental health presentations. The significant undercount indicates greater mental health demand than current figures suggest.